2004
DOI: 10.3139/217.1834
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Flexural Properties of β-Nucleated Polypropylenes

Abstract: Tensile and Flexural Properties of b-Nucleated PolypropylenesResuming our previous work on b-nucleated polypropylenes, namely on their impact strength, our present work directs attention towards a flexural and tensile behavior of b-nucleated polypropylenes (b-iPP). For the purposes of this work, commercially available isotactic polypropylene was modified using various amounts of a specific nucleating agent based on N, N 'dicyclohexylnaphtalene-2,6-dicarboxamide (NU100). From the prepared blends test specimens … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Furthermore, the a crystallization can be enhanced by addition of an a nucleating agent (NA), which can significantly improve the stiffness and yield strength of iPP (Fillon et al, 1993;Gahleitner et al, 2011). The NA can also easily shorten the induction time of the crystal nucleation and enhance the overall rate of transformation from molten polymer to crystalline (Chen et al, 2013;Obadal et al, 2004). However, if in a NA, the toughness will be reduced because of the compact structure formed in the a crystals (Li et al, 2012;Zamani et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the a crystallization can be enhanced by addition of an a nucleating agent (NA), which can significantly improve the stiffness and yield strength of iPP (Fillon et al, 1993;Gahleitner et al, 2011). The NA can also easily shorten the induction time of the crystal nucleation and enhance the overall rate of transformation from molten polymer to crystalline (Chen et al, 2013;Obadal et al, 2004). However, if in a NA, the toughness will be reduced because of the compact structure formed in the a crystals (Li et al, 2012;Zamani et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
“…The first resin, named HPP, was a homopolymer without nucleating agent. The second resin, named NPP, had sodium benzoate as nucleating agent in the concentration up to the critical concentration at which the β-form content reaches the saturation level 19,20,39 . Properties of both resins are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature [17][18][19][20][21] was revealed the promising mechanical properties of β-form in i-PP articles and it was also exposed that when special crystallization procedures are used or, in particular, specific nucleators as N,N'-dicyclohexylnaphthalene-2,6-dicarboxamide and sodium benzoate are added, the β-form can become as predominant crystalline form in common i-PP articles. Dong and cowokers 17 demonstrated that the sodium benzoate shows apparently versatile nucleating characteristic on the crystallization behavior of i-PP and that this nucleating activity is highly dependent on processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleation efficiency of NJS was proved by X-ray diffraction measurements and detailed calorimetric studies. ,− NJS proved to be an efficient nucleating agent also in production under industrial conditions. The β-phase content, or k value, of compression-molded, , extruded, and injection-molded parts produced with NJS is relatively high. The mechanical and other properties of the processed parts were determined as well.…”
Section: Introductionmentioning
confidence: 99%
“…In microsections, cut from processed samples, the occurrence of βα-recrystallization cannot be avoided. Thus, a smaller or larger melting peak of the α-iPP can be practically always observed on the melting traces of such samples. Consequently, conclusions drawn from calorimetric measurements done on samples cooled below must be treated with the utmost caution. , This note holds for those contributions which consider the melting peaks to estimate the amount of β-phase and its melting temperature. The critical evaluation of these results is again beyond the scope of this article.…”
Section: Introductionmentioning
confidence: 99%